"I also feel sad, because I can see that it’s getting worse and worse": Migraine patients’ perception of neck pain - Rosa, Milena Dietrich Deitos; Marçal, Jene Caroline Silva; Barros, Maria Luiza Santana; Costa, João Vitor Penteado; Barbosa, Ana Beatriz; Florencio, Lidiane Lima; Palacios-Ceña, Domingo; Dach, Fabiola; Grossi, Débora Bevilaqua- (Headache Medicine, 2024)
Introduction: There is a high prevalence of neck pain in patients with migraine, which when reported can show a worse clinical presentation of the disease, such as more prominent signs and symptoms and a worse psychological burden, reinforcing its impact. However, the way it is interpreted by patients is still little explored and known.Objective: To understand the relevance of neck pain for patients with migraine, observing their perception, beliefs and strategies for dealing with this symptom. Methods: This is a qualitative, descriptive and exploratory study, developed in accordance with the COREQ and SRQR, approved by the CEP (CAAE: 58915822.1.0000.5440). Twenty-four individuals aged between 18 and 55 diagnosed with migraine according to the 3rd edition of the International Classification of Headache Disorders and with self-reported neck pain took part in a semi-structured interview. The transcripts were subjected to thematic analysis and inductive coding. Results: Four themes emerged from the analysis: 1) Pain characteristics; 2) Pain beliefs; 3) Coping strategies; 4) Emotional aspects. Patients describe their pain as something rigid and locking, being an uncomfortable and very painful sensation. There is a diversity of opinions on the cause, some relating it directly to migraine and others to emotions and their body positioning. With regard to management, as the main prevention strategy, patients reported stretching and exercising. The coping strategies mentioned were active movements, self-massage and medication, such as common painkillers and muscle relaxants when the pain is strongest. These patients also reported not allowing neck pain to affect their routine activities. Emotions such as anxiety, sadness and frustration were mentioned. Conclusion: This study provides important insights into the views of patients with migraine regarding neck pain and their management strategies, but there is still a diversity of opinions regarding the understanding of the cause of neck pain. Professionals should include this condition in their clinical assessments, giving due attention to the craniocervical system, so that they can individually advise patients about this condition and how it should be managed, thus encouraging better choices.